Sea Oats, Uniola paniculata - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Sea oats occur throughout Florida on beach dunes and beaches and on coastal areas west to Texas and north to Maryland. Sea oats are vital dune builders that accumulate sand and prevent erosion due to wind, waves, and large storms. As sand is trapped by the long leaves of sea oats, vertical growth is stimulated, and rooting occurs at the buried nodes. This plant is extremely drought- and salt-tolerant, grows up to the high tide line of beaches, and propagates both vegetatively and by seed in the wild (Shadow 2007). https://edis.ifas.ufl.edu/sg186